Price dispersion and online markets maturity in Poland - Konopielko, Łukasz; Radkova, Diana (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
This paper is dedicated to the issue of persistent price dispersion in real markets in the context of Polish online market development. The two channels of retail (online and offline) are observed and compared with regard to price variations determinants and their values comparison. Market efficiency comparison between both markets is also provided on the basis of theoretical background. The data collected from shops representing the two channels of retail (online and offline), for a number of commodities within the home appliance product category in Poland, has been used as a sample for the analysis. Generally, results for the Polish market are in line with similar tests performed for EU as a whole and confirm the maturity of Polish online market.